Kajian Etnosains dalam Cap Go Meh Singkawang sebagai Media Pembelajaran IPA Kelas IV - Indah Pranata, Teofilus; Sulistri, Emi; Mariyam, Mariyam (PGSD STKIP PGRI Pacitan, 2024)
This research aims to: 1) identify the sounds that occur during the Cap Go Meh celebration in Singkawang City; 2) to describe the ethnoscience reconstruction of Cap Go Meh culture in science learning; 3) to describe the implementation of the ethnoscience learning process in the Cap Go Meh culture. The research used is qualitative research which uses observation and interviews. This research was conducted in the FOBI (Indonesian Barongsai Sports Federation) community, which is located at SMK Mudita Singkawang. The research results show that; 1) from the results of identifying the sounds on the Cap Go Meh musical instrument, there are elements of the basic sound properties of the three Cap Go Meh musical instruments; 2) reconstruction of the Cap Go Meh culture can be linked to learning because playing the Cap Go Meh musical instrument contains elements of the basic properties of sound; 3) implementation of the ethnoscience learning process in the Cap Go Meh culture can be implemented and collaborated in the form of lesson plans on core activities in delivery using audio-visual media.